New Orleans Women and the Poydras Home : More Durable than Marble - Tyler, Pamela (Book collections on Project MUSE., 2016)
"A two-hundred-year-old institution, the Poydras Home--originally the Poydras Asylum--stands as an exemplar of woman-led charitable organizations. In a thorough and engaging narrative, Pamela Tyler offers the first complete history of this remarkable New Orleans establishment from its founding as an orphanage for young girls to its present-day operation as a retirement community and assisted-living facility. Throughout, Tyler paints a vivid picture of the many women who faced down the challenges of war, disease, natural disaster, social unrest, and restrictive gender ideals to realize the mission of the Poydras Home. Drawing on previously unreleased archival material, Tyler documents how the institution's benefactor, Julien Poydras, used his immense wealth to support a haven for impoverished girls, and how the dedicated women of the Poydras board pursued that ambition through more than just residential services. Tyler reveals that the majority of the Poydras 'orphans' had one living parent, and it was dire poverty and a dearth of social services in New Orleans that drove single parents, usually mothers, to place their daughters in the asylum. Further research demonstrates that the Poydras went beyond simply providing a shelter for the children of distressed parents: volunteer managers worked to shape their charges' character through an emphasis on morals, education, and the fundamentals of housewifery"--Publisher's website.